Translingual practice in remote EFL tertiary education: How multilingual speakers create translanguaging spaces - Akhmad Hairul Umam; Setiono Sugiharto; Christine Manara (Indonesian Journal of Applied Linguistics, 2023)
Published studies on translingual practice in the pedagogical realms have burgeoned in the current literature, generating important insights into how communication has become dynamic and fluid. However, these studies have focused almost exclusively on face-to-face, in-person interactions. As COVID-19, which hit all domains of life (including education) worldwide, has compelled schools to conduct remote learning interaction, it will be more revealing to pursue further how translingual practice is enacted in a virtual classroom. Drawing on the notion of translingual perspective (Canagarajah, 2013), this study investigated how English as a Foreign Language (EFL) teachers and learners at tertiary education created a translingual space in their interactions by deploying specific negotiation strategies and various multimodal resources in a digital learning platform. Employing a netnography method and interactive model (Miles Huberman, 1994), this study employed virtual observation, surveys, and interviews as the sources of data. The study has revealed the complexity of translingual practices in EFL remote learning interactions that occurred naturally in different parts of teaching-learning activities. The use of verbal, semiotic, and multimodality resources as negotiation strategies for meaning-making plays essential roles in facilitating fluid and dynamic interactions. Pedagogically, the interaction in EFL remote learning has been found to be more multilaterally engaging.